Penerapan Protokol Kesehatan COVID-19 di Panti Asuhan Kecamatan Jambangan Kota Surabaya - Fadhillah, Annisa Nur; Thohari, Imam; Winarko, Winarko; Rusmiati, Rusmiati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
The implementation of the COVID-19 health protocol in orphanages is very important during the pandemic in order to prevent the spread of the virus among orphanages, considering that many people gather in orphanages to carry out activities. This study aims to describe the implementation of the COVID-19 health protocol in the Jambangan District Orphanage, Surabaya City in 2022. The research method used was observational, cross-sectional and descriptive analysis. Data were collected from the entire population in 4 orphanages, Jambangan sub-district, Surabaya, which amounted to 81 people. The data collected, processed and analyzed descriptively through table analysis. The results showed that compliance with the implementation of health protocols was 100% for the manager, 53.1% for foster children and 46.9% for non-compliance. It is recommended that the orphanage manager can carry out supervision and counseling on the importance of implementing health protocols, completing posters in the orphanage area and setting the distance for the residents of the orphanage during their activities.